The official Cambridge guide to IELTS for academic &​ general training : - Cullen, Pauline (Cambridge University Press, 2014)
The official Cambridge guide to IELTS' is THE definitive guide to IELTS. It contains all you need to succeed in the exam. Skill-building exercises cover all of the question types in the exam for both the General Training and Academic modules. Our research into real IELTS candidates' exam answers - and the mistakes they make, helps you avoid the same ones! Eight official practice tests and a focus on test-taking strategy help you maximise your score.